Trends in linguistic, scholastic and educational policies in trentino and Alto Adige (1919-1939) - Elisa Gori (Acta Scientiarum. Education, 2016)
The text proposes the examination of school and educational policy choices made in the territories of Trentino and Alto Adige, for German and Ladin speaking minorities in the time period between the end of the first major world conflict and the beginning of the second. During the historical period under consideration, the territories of the new provinces were headquarters and object of multiple political, economic and cultural operations, marked by different and opposite strategies: referrals of implicit nationalist trend which attributed extensive legislative powers to central authorities, were replaced by more democratic guidelines, that embraced local autonomies and recognized the rights of the minorities. Search for a political balance between the two instances, which was initially pursued, left the field with the arrival of the first fascist government to a new scenario with the aim of Italianize, even with the use of violence, the kind and organization of the new provinces. The same contradictory scenario will mark the evolution of educational policies in the new territories; the attempt to extend the Italian scholastic regulations to new provinces, first gradually and respectfully on the linguistic minorities, their schools and traditions, with the fascist government will suffer a significant change in behavior and reasoning. The theme of this research, which is little studied and analyzed in detail, assumes its relevance, whether in terms of historical and educational research linked to particular historic moment and geographical context, whether in terms of the consequences that it had in the construction of the Italian Republic.